PENGARUH PRODUK, HARGA, LOKASI, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN (Studi pada Apotek FAIZA di Kota Kendal) - Pranita, Hesti; Sutino, Sutino (Students Journal of Accounting and Banking, 2012)
This study aims to examine the effect of product, price, location, and promotion to the pharmacy customer satisfaction Faiza atKendal Town.The population in this study were all customers at the pharmacy Faiza. While sampling in this study using Purposive sampling,in anticipation of the damage or return of the questionnaire, the questionnaire is distributed as many as 100 exemplar, so that thesample set of 100 exemplar can be met.There are 4 hypotheses were tested in this study in which each will test the hypothesis of the influence of the Product, Price,Location, and Promotion of customer satisfaction in the city pharmacies FAIZA Kendal. Analysis tool used is the validity of the Test,Reliability Test, Multiple linear regression, the coefficient of determination, which includes the Test of Hypothesis Testing t. Testresults of validity of variables used in this study is valid, the results of reliability tests showed that the variables used in this study isreliable. the results of multiple linear regression that the product (X1), price (X2), location (X3), and promotion (X4) has a positivesignificant effect on customer satisfaction. The coefficient of determination (R Â²) that the value of Adjusted R Square, which meansthe variation of product changes (X1), price (X2), location (X3), and promotion ( X4) in influencing customer satisfaction.Hypothesis Test Results, Test t is a significant positive effect of product (X1), price (X2), location (X3), promotions (X4) to customersatisfaction.Key Word : Product, Price, Location, Promotion, and Customer Satisfaction.